2015
DOI: 10.1155/2015/863715
|View full text |Cite
|
Sign up to set email alerts
|

Pressor Response to Noradrenaline in the Setting of Septic Shock: Anything New under the Sun—Dexmedetomidine, Clonidine? A Minireview

Abstract: Progress over the last 50 years has led to a decline in mortality from ≈70% to ≈20% in the best series of patients with septic shock. Nevertheless, refractory septic shock still carries a mortality close to 100%. In the best series, the mortality appears related to multiple organ failure linked to comorbidities and/or an intense inflammatory response: shortening the period that the subject is exposed to circulatory instability may further lower mortality. Treatment aims at reestablishing circulation within a “… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 54 publications
1
19
0
Order By: Relevance
“…; Geloën et al. ). Nevertheless, dexmedetomidine improved vascular reactivity to phenylephrine, through a mechanism that largely remains to be determined.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Geloën et al. ). Nevertheless, dexmedetomidine improved vascular reactivity to phenylephrine, through a mechanism that largely remains to be determined.…”
Section: Discussionmentioning
confidence: 97%
“…; Geloën et al. ). Geloën and coworkers reported that rats challenged with lipopolysaccharide (LPS) had decreased pressor responses to noradrenaline that could be entirely restored by clonidine and dexmedetomidine (Geloën et al.…”
Section: Introductionmentioning
confidence: 97%
“…In septic shock, reversal of hypotension with the currently available vasoconstrictors is limited by tachyphylaxis because vasoconstriction diminishes as treatment continues, resulting in inadequate blood perfusion and vital organ failure. It has been proposed that the loss of vasoconstriction due to α 1 -adrenoceptor agonists in septic patients might result from receptor desensitization (Geloen et al, 2015;Hwang, Lau, Huang, Chen, & Liu, 1994), and again, the development of ligands that are less tachyphylactic than the natural catecholamines and phenylephrine would be a significant improvement in the emergency treatment of hypotension by providing more sustained elevation of BP. through Gq proteins and, probably, through β-arrestins, leading to the activation of MAPKs, modulation of transcription factors, and ultimately to hypertrophy (Cotecchia et al, 2015;O'Connell et al, 2014;Woodcock et al, 2008).…”
Section: α 1 -Adrenoceptors In Arteriesmentioning
confidence: 99%
“…Recently, studies have shown that DEX has potent anti-inflammatory, antioxidant and anti-apoptotic effects [11][12][13]. Animal studies have suggested that DEX plays a protective role in a number of lung diseases, including ALI [14][15][16].…”
Section: Introductionmentioning
confidence: 99%